Activated partial thromboplastin time-based clot waveform analysis: a potential for application in acute myocardial infarction and its complications - Chen Lin Ng; Felix Maverick Uy; May Anne Cheong; Wan Hui Wong; Yee How Lau; Heng Joo Ng; Khung Keong Yeo; Chuen Wen Tan (Scientific Reports)
Abstract Activated partial thromboplastin time (aPTT)-based clot waveform analysis (CWA) is a plasma-based global haemostatic assay. Elevated CWA parameters have been associated with hypercoagulability in venous thromboembolism, but its role in arterial thrombotic disease is uncertain. This study aims to explore the relationship between aPTT-based CWA and acute myocardial infarction (AMI) and its complications. In a retrospective cohort study of patients with AMI who underwent emergency cardiac catheterisation, pre-procedural aPTT and CWA parameters—min1, min2 and max2 were measured. These were compared against a control group of patients, consisting of patients who underwent elective orthopaedic and urological procedures. Within the AMI cohort, we also compared aPTT and CWA parameters of those with and without clinical complications of AMI. Results: Compared to controls (N = 109), patients with AMI (N = 214) had shorter aPTT (26.7 ± 3.3 s vs 27.9 ± 1.7 s, P < 0.001) and higher CWA parameters (min1: 6.11 ± 1.40%/s vs 5.58 ± 1.14%/s; min2: 0.98 ± 0.23%/s2 vs 0.90 ± 0.19%/s2; max2: 0.81 ± 0.20%/s2 vs 0.74 ± 0.16%/s2, all P ≤ 0.001). There was an increased incidence of elevated CWA parameters, in the AMI group, with odds ratio (OR) of 2.06 [95% CI 1.10–3.86], 2.23 (95% CI 1.18–4.24) and 2.01 (95% CI 1.07–3.77) for min1, min2 and max2, respectively. Similarly, elevated min1 and min2 were both individually associated with the presence of adverse outcomes of AMI, both with ORs of 2.63 (95% CI 1.24–5.59). Elevated aPTT-based CWA parameters are significantly associated with the occurrence of AMI and its complications. These findings identify the potential utility of CWA as risk and prognostic markers for AMI and warrants future works.